Evolution of a Relativistic Electron Beam for Tracing Magnetospheric Field Lines - Powis, Andrew T.; Porazik, Peter; Greklek-Mckeon, Michael; Amin, Kailas; Shaw, David; Kaganovich, Igor D.; Johnson, Jay; Sanchez, Ennio (Frontiers in Astronomy and Space Sciences, 2019)
Tracing magnetic field-lines of the Earth's magnetosphere using beams of relativistic electrons will open up new insights into space weather and magnetospheric physics. Analytic models and a single-particle-motion code were used to explore the dynamics of an electron beam emitted from an orbiting satellite and propagating until impact with the Earth. The impact location of the beam on the upper atmosphere is strongly influenced by magnetospheric conditions, shifting up to several-degrees in latitude between different phases of a simulated storm. The beam density cross-section evolves due to cyclotron motion of the beam centroid and oscillations of the beam envelope. The impact density profile is ring shaped, with major radius $\sim 22$ meters, given by the final cyclotron radius of the beam centroid, and ring thickness $\sim 2$ meters given by the final beam envelope. Motion of the satellite may also act to spread the beam, however it will remain sufficiently focused for detection by ground-based optical and radio detectors. An array of such ground stations will be able to detect shifts in impact location of the beam, and thereby infer information regarding magnetospheric conditions.